THE IMPACT OF FIRST LANGUAGE ON SECOND LANGUAGE ACQUISITION: TRANSFER AND INTERFERENCE - Fitri, Raisa; Alawiyah, Tuti (Transpublika Publisher, 2023)
This study aims to explore the impact of first language (L1) on second language (L2) acquisition, focusing on the phenomena of transfer and interference. The background of the problem shows that second language learning is often a complex process, influenced by similarities and differences between the first and second languages. Positive transfer occurs when first language elements facilitate second language learning, while negative interference arises when language differences cause errors or difficulties in the learning process. The research method used is a qualitative descriptive design, with data collected from various relevant academic literature, such as journals, books, and research articles. The results show that transfer from the first language to the second language can have both positive and negative impacts depending on the similarities between the two languages. In addition, social, cultural and psychological factors such as age, anxiety and motivation also affect the level of first language interference. Older learners tend to experience greater interference compared to younger learners. These findings emphasize the importance of teaching strategies that can capitalize on the positive transfer and minimize the negative impact of first language interference in the second language learning process.